OpenStudy (anonymous):

(4a - b) + (3a - 5b)

5 years ago
OpenStudy (anonymous):

4a-b+3a-5b= 7a-6b

5 years ago
Parth (parthkohli):

I went through an exact same question yesterday. Though I'll answer it. Open the brackets. \(\Large \color{MidnightBlue}{\Rightarrow 4a - b + 3a - 5b }\) Operate on the like terms. \(\Large \color{MidnightBlue}{\Rightarrow (4a + 3a) + (-b -5b) }\) \(\Large \color{MidnightBlue}{\Rightarrow 7a - 6b }\)

5 years ago
OpenStudy (anonymous):

Thanks.

5 years ago
Parth (parthkohli):

:)

5 years ago
Similar Questions: